A review on supercritical fluid extraction as new analytical method - Abbas, Kassim Ali; Mohamed, A.; Abdulamir, Ahmed Sahib; Abas, H. A. (Science Publications, 2008)
This review study summarized the Supercritical Fluid Extraction (SFE) as new analytical method. The advantage and disadvantage of CO2 (SC-CO2 )as well as special applications of SFE in food processing such as removal of fat from food, enrichment of vitamin E from natural sources, removal of alcohol from wine and beer, encapsulation of liquids for engineering solid products and extraction and characterization of functional compounds were also highlighted. The study also covered the application of SFE in food safety such as rapid analysis for fat content, rapid analysis for pesticides in foods as well as the recent applications of SFE in food such as supercritical particle formation and nan particle formation and ssupercritical drying. The outcome finding confirmed that SFE was found to be advance, fast, reliable, clean and cheap methods for routine food analysis.